A bibliometric analysis on renewable energy microgrids integrating hydrogen storage: Strategies for optimal sizing and energy management - Mukhtar Fatihu Hamza; Babangida Modu (Scientific African)
Hydrogen is regarded as a viable alternative energy carrier because of its superior energy density and low emissions, with great potential for decarbonizing multiple sectors and improving energy sustainability by integrating into the existing energy systems and renewable energy source within the utility. This paper provides a bibliometric assessment through an extensive review of highly cited articles on hydrogen storage integrated microgrid. The study utilized the Web of Science (WoS) database to look for specific keywords related to hydrogen storage integrated microgrid and associated research. The findings reveal that optimization, highly positioned and connected to many other keywords, is demonstrating its importance in the research area. Notable insights highlight the dominance of simulation-based studies, a significant number of publications in top-tier journals, and the rise of innovative research fields, including the creation of sustainable electrodes and improvements in system reliability and efficiency. The evaluation of the articles that are highly cited sheds light on diverse elements, such as approach and system, challenges, and research spaces. This analysis shows ways to improve the performance of operation, energy efficiency, environmental sustainability, cost-effectiveness, stable supply of power, on-location energy generation, and flexibility, thereby advancing technological innovation and fostering the development of hydrogen storage-integrated microgrids.